New South Wales - Barton, Roberta (Port Melbourne : Heinemann Library, 2003)
Each title in this series examines one Australian state or territory in depth. Each book begins by documenting the early history and then provides a comprehensive overview of the state today. Topics covered include government, geography, industry, tourism, recreation, education, the environment and the arts.
Includes index.
Bibliography.
For primary and secondary students.
Keywords: New South Wales -- Juvenile literature